WERECLAIM: A MERN Stack Solution to Enhance the Online Resale Market - T.H.C. Heshan; J.M.S.U. Jayasinghe; T.O.M. Dharmaratne; D.K. Hiththatiyage; D.I. De Silva; S.P. Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
Since the days of trading, used items have been widely used and recently, the marketing of these secondhand goods has received increased attention. Shopping ethically or acting ethically as a consumer has grown in popularity along with the rise in demand for used goods. People now prefer doing business online over the conventional means of satisfying their wants due to the huge advancement of technology. Furthermore, given that there are many who are unemployed and wish to earn money online, this kind of platform for buying and selling old goods is timely to address those needs as well. Making a platform for used goods sales and purchases appears to be an excellent idea in the age of digitization and WERECLAIM was designed to address several issues of purchasing and selling goods in the secondhand market. The purpose of this study is to investigate the major trends of used items buying and selling platforms and to emphasize the contribution of WERECLAIM to the modern used goods, buyers, and sellers. We have identified the major issues and the current needs of a used items trading system and came up with the system WERECLAIM which fulfills the demand of a used items trading platform.